Unsteady Al2O3-Cu/H2O hybrid nanofluid flow over a rotatable stretching disk with heat generation and deceleration: stable dual solutions - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi’ie, Najiyah Safwa; Pop, Ioan (Informa UK Limited, 2023)
This study reveals the impact of heat generation and variable strength of rotation on the unsteady flow of a hybrid nanofluid over a rotatable disk with stretching characteristics and deceleration. A novel mathematical model specifically tailored to elucidate the behavior of a hybrid nanofluid is proposed. By employing similarity variables, the governing model is reformulated into ordinary differential equations (ODEs). The bvp4c function (MATLAB) is employed to efficiently obtain the numerical solutions of these ODEs. To provide a comprehensive study, a stability analysis is also conducted to investigate the properties associated with the non-unique dual solutions generated by the model. Dual solutions are generated, and both are analyzed to be stable. A lower amount of heat generation with greater disk rotation strength is recommended to further improve the heat transfer rate of the model. The bifurcation point is absent within the setup ranges of the parameters in the present study, which suggests a well-maintained laminar flow simulation. The findings of this study offer valuable insights and can assist other researchers in improving their understanding and modeling of similar fluid flow systems, particularly hybrid nanofluid flow systems.